Analysis of Literacy and Numeracy Skills of Senior High School Students at Pandeglang - Pancawardani, Regia Manik; Nufus, Hayati; Survani, Rifki; Hurotulaeni, Heni (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
According to PISA data, Indonesian students' literacy and numeracy skills rank 73rd and 74th out of 79 countries, respectively. This indicates a low level of literacy and numeracy among students in Indonesia. Therefore, innovative approaches in education are needed to enhance these skills. One such approach is fostering a school culture of literacy and numeracy, as implemented at one of the senior high schools in Pandeglang. This study aims to analyze the literacy and numeracy skills of Pandeglang 10th High School students. The research employs an ex post facto method with a descriptive approach. Data collection was conducted through literacy and numeracy tests administered to 10th-grade students. The analysis reveals that students' literacy skills are relatively good, while their numeracy skills tend to be low. Nevertheless, there has been a significant improvement in both aspects, with steady monthly progress in literacy and numeracy skills. Thus, sustaining literacy and numeracy activities as a school culture is crucial to achieving better outcomes.